Determinan Pemeriksaan Payudara pada Mahasiswa STIKes Dharma Husada Bandung - Tuti Surtimanah; Irfan Nafis Sjamsuddin; Metha Dwi Tamara (Sehat MasadaJurnal, 2020)
Background: In 2018 global data showed 24.2% new cases of breast cancer in women with 15% died, while in Indonesia 58,256 new cases of breast cancer with 22,692 died. Breast cancer at a young age has a unique clinical and biological picture is more aggressive with an unfavorable prognosis, so the breast examination at a young age is very important. Institute of health students are young people as prospective health workers need to give examples in breast examination, where it didn’t known how the breast examination is done so far. Objective: To determined the determinant factors and practiced of breast examination.. Methods: A cross-sectional study design with data collection through filled out questionnaires about breast examination, breast cancer literacy, individual characteristics. Data were analyzed univariate, bivariate, and multivariate. Results: As much 55.6% students had a high level of literacy about breast cancer. Literacy and gender are determinants of breast self-examination, literacy and family cancer history are determinants of clinical breast examination, age is a determinant of breast ultrasound practiced. Path analysis shows the direct effect of literacy on breast examination at the intermediate level. Research results are expected to be useful in compiling messages to increase breast cancer literacy as a determinant that can be sought to change